Psychological Well-Being Among Correctional Inmates in Kupang Class IIB Women’s Prison Seen From Forgiveness and Spirituality - Neonufa, Adriana; Shanti, Pravissi (Jurnal Sains Psikologi, 2023)
Correctional inmates who have to serve prison terms face various problems such as negative self-acceptance, limited freedom, negative feelings that arise, and negative stigma from the environment, which negatively impacts psychological well-being, so they need forgiveness and spirituality to improve psychological well-being. This research aims to determine the influence of forgiveness and spirituality on the psychological well-being of correctional inmates in the Kupang Class IIB Women’s Prison, both partially and simultaneously. The research method used is quantitative with a correlational type. The respondents of this research were 57 correctional inmates in the Kupang Class IIB Women’s Prison. The instruments used are the forgiveness, spirituality, and psychological well-being scales. The validity test in this research used content validity and instrument reliability using Cronbach’s alpha formula in the high category. Hypothesis testing uses simple linear regression analysis and multiple linear regression analysis. The results obtained in this research show that forgiveness and spirituality simultaneously influence psychological well-being with an F value of 11.559 and p equal to 0.000 (p less than 0.05) with an effective contribution of 30 percent. Partially, forgiveness significantly influences psychological well-being by 28 percent, with p equal to 0.000 (p less than 0.05). Spirituality significantly influences psychological well-being by 11.7 percent, with p equal to 0.009 (p less than 0.05).